Pembelajaran Bahasa Arab di Indonesia: Problematika dan Solusi Prespektif Sosiokultural Vygotsky - Alfan Afifi Kurniawan; Bahrul Ilmi; Nailul Authar; Wildana Wargadinata (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2022)
The purpose of this study is to reveal the problems found in the process of learning Arabic. These problems and solutions will be reviewed from a sociocultural perspective a la Vygotsky. The research method used is the qualitative method of literature. The data presented comes from several sources such as books and research articles related to research objectives. The result of this study is that Vygotsky's theory is based on three main aspects, namely genesis, Zone of Proximal Development (ZPD), and mediation. There are three problems in learning Arabic according to sociocultural theory, namely sociocultural differences, lack of interaction in Arabic, and a lack of Arabic language environment. While the solution to these problems is multicultural-based, activity-based, and environment-based learning planning.